Effects of 1,25-dihydroxycholecalciferol on calcium absorption, muscle weakness, and bone disease in chronic renal failure. - Henderson, R; Russell, R; Ledingham, J; Smith, R; Oliver, DO; Walton, R; Small, D; Preston, C; Warner, G (1974)
Small amounts (0.35-2.7 μg.) of 1,25 dihydroxycholecalciferol (1,25-D.H.C.C.), the hormonally active metabolite of vitamin D3, were given to eleven patients with chronic renal failure for 4-150 days. 1,25-D.H.C.C. given for 4-8 days increased intestinal 47Ca absorption without causing large changes in plasma calcium or phosphate, or in plasma or urine hydroxyproline measurements. 1,25-D.H.C.C. was given for a longer period (58 and 150 days) to two of the patients. In one, a 14-year-old girl, plasma alkaline phosphatase and non-protein bound hydroxyproline fell and there was healing of radiological rickets and secondary hyperparathyroidism; and in the other, a man of 58 years, there was striking improvement in muscle weakness. The resistance to treatment with vitamin D in chronic renal failure is probably related to impaired metabolic conversation to active derivatives, the most important of which may be 1,25-D.H.C.C. 1,25-D.H.C.C. seems capable of correcting some, if not all, of the disturbances in calcium metabolism in this disorder. © 1974.